Tłumacze literatury polskiej w świetle Słownika słowackich tłumaczy literatury pięknej - Pojezdalová, Zuzana (Przekłady Literatur Słowiańskich, 2016)
Translators of Polish Literature as reflected in the Dictionary of Slovak Literary Translators of the 20th Century The author of this paper introduces the Dictionary of Slovak Literary Translators of the 20th Century of which Veda Publishing House published the first volume in 2015. The paper deals with the structure and contents of the dictionary and it focuses on the translators of Polish literature. The author explores seven translators who predominantly work on translations from the Polish language and she introduces their profiles — from the point of view of study, language education and profession. She also pays attention to literary critics’ reviews and defines their poetics as well. She concentrates primarily on Karol Chmel, who is one of the best -known translators of Polish literature in Slovakia, and who occupies the leading position in this field. Key words: dictionary, Slovak translators, literary translation, Karol Chmel